AKTIVITAS ANTIOKSIDAN PADA BIJI KOPI ARABIKA (COFFEA ARABICA L.) DARI TIGA DAERAH BERBEDA DENGAN METODE 2,2-DIPHENYL-1-PICRYLHYDRAZIL (DPPH) DAN 2,2â-AZINO-BIS-3-ETHYLBENZOTHIAZOLINE-6-SULFONIC ACID (ABTS) - Annisa
Free radicals are compounds or molecules that contain one or more unpaired electrons. Due to unpaired electrons, free radicals are very reactive in finding electron pairs by attacking and binding to surrounding electrons. Reactivity of free radicals may cause degenerative diseases in human. Free radicals can be scavenged by using antioxidants. Antioxidant compounds have been found in several species of plants, for example in coffee beans. The objectives of this research were to study antioxidant activities of Arabica coffee beans from three different regions, Toraja, Lintong and Mandailing using two methods of antioxidant assays which were DPPH and ABTS assays, determine total phenolic, flavonoid, and carotenoid content; correlation of total phenolic, flavonoid, and carotenoid with their IC50 DPPH and ABTS, and correlation between the antioxidant activities between the two testing methods DPPH and ABTS. Extraction was performed by reflux using gradient polarity solvents, namely n-hexane, ethyl acetate, and ethanol, respectively. Extracts were monitored by thin layer chromatography (TLC). Determination of IC50 of DPPH and ABTS scavenging activities, total phenolic, flavonoid, and carotenoid content were performed by UV-Vis spectrophotometry and their correlation with DPPH and ABTS scavenging activities by ????±•???????????????????±????í?. Ethanolic Arabica coffee beans extract from Lintong had the lowest IC50 of DPPH scavenging activities (0.7 µg/mL) and the lowest IC50 of ABTS scavenging activities was given by ethyl acetate Arabica coffee beans extract from Mandailing (1.66 µg/mL). Ethanolic Arabica coffee beans extract from Mandailing had the highest phenolic content (70.55 g GAE/100 g), ethyl acetate Arabica coffee beans extract from Mandailing had the highest flavonoid content (7.41 g QE/100 g) and ethanolic Arabica coffee beans extract from Lintong had the highest carotenoid content (0.28 g BE/100 g). Total phenolic content and total carotenoid content in Arabica coffee beans extract from Lintong had negative and high correlation with their IC50 of DPPH scavenging activities. There were linear correlation between IC50 of ABTS scavenging activities and IC50 of DPPH scavenging activities of coffee beans extract from Lintong. Phenolic compounds and carotenoid compounds in coffee beans extract from Lintong were the major contributor in IC50 of DPPH scavenging activities. DPPH and ABTS methods gave linear result in antioxidant activity of Arabica coffee beans extract from Lintong.